2022
DOI: 10.3389/fimmu.2022.1010911
|View full text |Cite
|
Sign up to set email alerts
|

Progress of cGAS-STING signaling in response to SARS-CoV-2 infection

Abstract: Coronavirus disease 2019 (COVID-19) is an epidemic respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that can cause infections in millions of individuals, who can develop lung injury, organ failure, and subsequent death. As the first line of host defense, the innate immune system is involved in initiating the immune response to SARS-CoV-2 infection and the hyperinflammatory phenotype of COVID-19. However, the interplay between SARS-CoV-2 and host innate immunity is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Studies have shown that the cGAS-STING pathway plays an important regulatory role in the regulation of autophagy, ferritinophagy, ferroptosis, and inflammation [ 64 67 ]. In addition, studies on alleviating lung injury by inhibiting the activation of the cGAS-STING pathway have been reported, but the literature is relatively few [ 35 37 , 68 ]. In this study, by silencing cGAS, it was found that the activation of the cGAS-STING pathway in BLM-induced lung epithelial cells was inhibited, and the levels of autophagy and ferroptosis were also decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the cGAS-STING pathway plays an important regulatory role in the regulation of autophagy, ferritinophagy, ferroptosis, and inflammation [ 64 67 ]. In addition, studies on alleviating lung injury by inhibiting the activation of the cGAS-STING pathway have been reported, but the literature is relatively few [ 35 37 , 68 ]. In this study, by silencing cGAS, it was found that the activation of the cGAS-STING pathway in BLM-induced lung epithelial cells was inhibited, and the levels of autophagy and ferroptosis were also decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Since oxidative stress markers were not altered in this study, we suggest that DNA damage in COVID-19 patients might be driven by inflammation. Mechanistically, the cGAS-STING pathway plays a pivotal role in the detection of foreign genetic material including viruses such as SARS-Cov-2 [ [68] , [69] , [70] ] and consequently induces immune responses. However, a prolonged activation of this pathway might enhance the risk for chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…114 For example, certain viral proteins have been discovered that obstruct cGAS LLPS, thereby blocking its activation and facilitating immune evasion by the virus. 114 Furthermore, the activation of the DNA sensing protein cGAS and its downstream effector STING can trigger a type-I IFN response in the context of SARS-CoV-2 infection. This implies that cells have the ability to detect SARS-CoV-2 infection and initiate an IFN response, even though the virus can evade certain components of the innate immune system.…”
Section: Phase Separation: Decoding Cgas-sting Pathwaymentioning
confidence: 99%
“…There is substantial evidence to suggest that SARS‐CoV‐2, a single‐stranded positive‐sense RNA virus, instigates the cGAS‐STING signaling pathway. Viruses, SARS‐CoV‐2 among them, have adapted to exploit LLPS for immune evasion 114 . For example, certain viral proteins have been discovered that obstruct cGAS LLPS, thereby blocking its activation and facilitating immune evasion by the virus 114 .…”
Section: Sars‐cov‐2 Nucleocapsid Protein Phase Separation Drives Pers...mentioning
confidence: 99%
See 1 more Smart Citation